A Study on Mathematics Learning Achievement in Systems of Linear Equations with Two Variables Using the Brainstorming Technique for Third-Year Secondary School Students at the Demonstration Secondary School of Savannakhet Teacher Training College - LEUANG, Vilai; Kanorth, Panyda (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aimed to examine the effects of the brainstorming teaching technique on students’ learning outcomes in mathematics, specifically focusing on the topic of systems of linear equations in two variables. It also sought to explore students’ satisfaction with learning through this method. The participants were 24 third-year high school students from Class 3/1 at Savannakhet Teachers’ College Demonstration School during the 2024–2025 academic year. The sample was selected through purposive sampling. The research instruments included a lesson plan based on the brainstorming technique, a mathematics achievement test, and a student satisfaction questionnaire. Data were analyzed using mean, standard deviation, and paired-sample t-test. The results revealed that: (1) students’ post-test scores were significantly higher than their pre-test scores at the 0.05 level, and (2) students reported a high level of satisfaction with learning mathematics through the brainstorming technique (M = 4.30, SD = 0.21). These findings suggest that the brainstorming teaching technique can enhance students’ learning outcomes and foster a positive learning experience.